2008
DOI: 10.1136/adc.2007.117713
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of two round neonatal resuscitation masks: study 1

Abstract: We compared a new neonatal face mask with an established design and found no difference in leak. On average the mask leak was >50% irrespective of operator experience or technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 6 publications
10
84
0
4
Order By: Relevance
“…No study has so far investigated the effect of predefined leak and different RRs on PIP, PEEP, and V t on ventilation parameters. Wood et al [7] compared different neonatal face masks using a manikin and described leaks ranging from almost zero to 100% (mean leak of 55–57%, depending on the mask). In other in vitro studies, Tracy et al [10] found mean leaks of 32%, while O’Donnell et al [8] detected mean ± SD leaks of 65 ± 33% and Schilleman et al [5] described a median of 71% leak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No study has so far investigated the effect of predefined leak and different RRs on PIP, PEEP, and V t on ventilation parameters. Wood et al [7] compared different neonatal face masks using a manikin and described leaks ranging from almost zero to 100% (mean leak of 55–57%, depending on the mask). In other in vitro studies, Tracy et al [10] found mean leaks of 32%, while O’Donnell et al [8] detected mean ± SD leaks of 65 ± 33% and Schilleman et al [5] described a median of 71% leak.…”
Section: Discussionmentioning
confidence: 99%
“…Today, SIBs and pressure-limited devices (so-called T-piece resuscitators) are commonly used for manual neonatal ventilation, and facemasks are most often used as the interface between the patient and the resuscitation device [1,3,4]. However, considerable leak has been shown to occur when operators with all levels of experience hold the mask on the infant’s face [5,6,7,8,9,10]. Such leaks were found to be underestimated, and were usually not corrected by the operator [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal prongs may be a more effective device than face masks for providing respiratory support after birth (LOE 2 53 ). There is insufficient evidence to support or refute the use of one type of mask over another for achieving clinical outcome, except that the Rendell-Baker style mask is suboptimal in achieving an adequate seal when used for newborns (LOE 5 54 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…5 However, during the application of manual positive-pressure ventilation (PPV) to infants, leaks around the face mask are common and obstruction of the upper airway may occur, leading to inadequate ventilation. [6][7][8][9][10] Mask leak and obstruction during mask PPV are often not recognized. 8,9,11 They may compromise the delivery of the set positive end-expiratory pressure (PEEP) and appropriate tidal volumes, resulting in delayed establishment of effective gas exchange.…”
mentioning
confidence: 99%